Prevalence and determinants of digital eye strain among school children during the COVID-19 pandemic - Simon, Catherine; Paul, Shalet (International Journal Of Community Medicine And Public Health, 2021)
Background: Digital eye strain (DES) is an emerging public health problem due to continuous exposure to electronic gadgets and digital devices for educational, occupational or entertainment purposes, especially during this COVID-19 pandemic. Children are more vulnerable to DES, as they continue to attend online classes but are unaware of early symptoms of DES and do not complain till their vision deteriorates. The objective of this study was to assess the prevalence and risk factors of DES among school children during this pandemic. Methods: A questionnaire-based cross-sectional study was conducted among 176 school children aged 12-16 years, studying in 8th, 9th and 10th standards of a randomly selected school in Kollam district of Kerala, using the validated computer vision syndrome questionnaire (CVSQ), sent online via Google form to parents/guardians for recording their children’s pattern of digital device usage and DES symptoms. Results: The prevalence of DES among school children was 29.5%. Their commonest symptom was headache (n=125, 69.9%). The smartphone was the most commonly used digital device (n=159, 93.5%). The independent risk factors of DES were the preferred use of smart phone (adjusted odds ratio (AOR)=2.846; 95% CI=1.371-5.906; p=0.005) and viewing distance of digital device <18 inches (AOR=2.762; 95% CI=1.331-5.731; p=0.006). Conclusions: This study has highlighted some of the risk factors associated with DES. A concerted effort is needed to raise awareness about DES by experts in the health and education sectors, along with parents and teachers, so that digital device use among children can be optimised.